Clinical study on the relationship between TCM wind-dampness syndromes and renal pathological activity in lupus nephritis - WANG Yue; LU Ying (Linchuang shenzangbing zazhi)
Objective Through the measurement and analysis of the clinical activity and renal pathological data,in combination with Wind-dampness syndromes,to approach the relationship between them.Methods According to the standards of TCM,divide 81 LN patients into 2 groups:Wind-dampness syndromes group and non-Wind-dampness syndromes group.Clinical data,renal pathology were collected.Analyze the correlation between Wind-dampness and these parameters.Results The Wind-dampness syndromes group had significantly higher number of patients with Ⅳ type LN(52.17%vs 22.85%,P<0.05),and it also had higher renal disease activity index(AI) than the nonWind-dampness syndromes(P<0.05).And it had more patients whose AI >10 than the non-Winddampness syndromes group.In particular,it was more obvious to find neutrophil infiltration,cellular crescent,tubular epithelial cell necrosis in Wind-dampness group.But we didn’t find difference in distribution of immunofluorescence of kidney disease management and chronic index(CI).The Winddampness syndromes group had much higer SLEDAI score(15.16 ± 5.43 vs 9.15 ± 4.69,P<0.05),and lower eGFR level(80.79 ± 36.38 vs 102.66 ± 39.89,P<0.05) than the non-Wind-dampness sydromes group.The Wind-dampness sydromes group had much more number of patients who had low complement,high level of urinary protein and white blood cells in urine than the non-Wind-dampness sydromes group.The level of AI was positively correlated with the level of 24-hour urine protein,urine red blood cells integral,and SLEDAI score,urine red blood cells integral and negatively correlated with the level of eGFR Conclusions The Wind-dampness syndromes in LN is closely related with the activities of nephritis disease activity index.The patients with Wind-dampness syndromes are much likely to have clinical activities,which means the Wind-dampness syndromes may be the basic material of the acute immune and inflammatory lesions in lupus nephritis.It is suggested that we should pay more attention to treat the Wind-dampness syndromes.